PENGARUH BEBERAPA PUPUK ORGANIK DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Mestika Hutagalung; Husna Yetti; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to get the interaction of organic manure and NPK fertilizer and determine the best treatment on growth and yield of shallot. The were research has been conducted on Randomized Completely Design Factorial. The first factor was the organic manure consist of without organic fertilizer (P0), chicken manure (P1), compost of empty fruit bunches oil palm (P2), vermicompost (P3) and rice straw compost (P4). The second factor was NPK fertilizer consist of three levels were without NPK fertilizer (N0), 10 g/m2 of NPK fertilizer (N1), and 20 g/m2 of NPK fertilizer (N2). Data analysed statistically with ANOVA and further tested using by Duncan`s New Multiple Range Test (DNMRT) of 5%. The parameters observed were plant height, number of leaves, convolution of tuber, number of tubers per clumps, fresh weight of tubers per m2 and proper saving of tubers per m2. The results showed the application of organic manure and NPK fertilizer significantly affected on the plant height, number of leaves, convolution of tuber, number of tubers per clumps, fresh weight of tubers per m2 and weight of tubers shelf per m2.  Application of rice straw compost and 20 g/m2 of NPK fertilizer delivered the best growth and yield of shallot. Keywords: shallot, NPK fertilizer, chicken manure, vermicompost and rice straw compost